Late Cretaceous thrips (Thysanoptera) from Hti Lin amber - Ulitzka, Manfred R. (Zootaxa, 2024)
The present study provides a first investigation of fossil thrips from the Late Cretaceous. It deals with two specimens—Avithrips yellae gen. et sp. n. and Campanithrips kyakhei gen. et sp. n.—which are preserved as inclusions in Campanian Hti Lin (or Tilin) amber from Myanmar. Their taxonomic classification in the families Melanthripidae and Stenurothripidae, as well as an adhering pollen grain suggest that both thrips may have been associated with flowers.